Both Terminal Oxidases Contribute to Fitness and Virulence during Organ-Specific Staphylococcus aureus Colonization - Friedrich Götz; Sonja Mayer (mBio, 2013)
ABSTRACT In their recent article, Hammer et al. (N. D. Hammer, M. L. Reniere, J. E. Cassat, Y. Zhang, A. O. Hirsch, M. Indriati Hood, and E. P. Skaar, mBio 4:e00241-13, 2013) described the dual functions of the two terminal oxidases encoded by cydBA and qoxABCD in Staphylococcus aureus. The aerobic growth of cydB or qoxB single mutant bacteria was barely affected. However, a cydB qoxB double mutant was completely unable to respire and exhibited the small-colony variant phenotype that is typical of menaquinone and heme biosynthesis mutants. The authors found that the two terminal oxidases play a role in pathogenesis. In a systemic mouse infection model, it turned out that in the cydB mutant the bacterial burden was significantly decreased in the heart, kidneys, and liver, while in the qoxB mutant it was decreased only in the liver. These results illustrate that both terminal oxidases contribute to fitness and virulence, representing promising candidates for the development of antimicrobials.